The Increasing Production of Soybean Plants (Glycine max L.) Based on Result Target’s and Nutrient Index - Michael Gusman Sianturi; Erwin Masrul Harahap; Hamidah Hanum (Jurnal Pertanian Tropik, 2019)
The aim of this research was to prove the giving fertilizer with dosage that produces seed production of soybean (Glycine max L.) 3 ton/ha and studying soil fertility through the nutrient indexs. The research was conducted in June 2017 until September 2017 at the market land of 1 Tanjung Sari, Medan Selayang sub-district. The research design is Factorial Random Design with two factors. The first factor is doses of fertilizer with the target of P1 = target 2 ton/ha; P2 = target 3 ton/ha; P3 = target of 4 ton/ha, second factor is treatment of soil nutrient index consist of B1 = 0,8 (100% less 20%); B2 = 0.9 (100% less 10%); B3 = 1 (100% standard nutrient index); B4 = 1.1 (100% plus 10%); B5 = 1.2 (100% plus 20%). The results showed that interaction of fertilizer based result target dose 3 ton/ha and nutrient index 0,9 (Urea : 45 kg/ha, SP-36: 90 kg/ha, KCL: 27 kg/ha, Phonska: 90 kg/ha, Dolomite: 900 kg/ha) reaches production of 2.86 tons/ha. The soil nutrient index found in B2 = 90% (fertilizer dose reduced by 10%) showed that the soil was fertile and gave the nutrient 10%.